Transformation pathways and fate of engineered nanoparticles (ENPs) in distinct interactive environmental compartments: A review. (May 2020) - Abbas, Qumber; Yousaf, Balal; Amina; Ali, Muhammad Ubaid; Munir, Mehr Ahmed Mujtaba; El-Naggar, Ali; Rinklebe, Jörg; Naushad, Mu
Highlights: Discharge of wastewater is the most important entry route of NPs in the environment. NPs are derived away from their pristine state through various dynamic transformations. Biological, physical and chemical transformations are interconnected. Transformation is regulated by NPs characteristics and environmental conditions. In the natural environment, NPs undergoes multiple transformations simultaneously. Abstract: The ever increasing production and use of nano-enabled commercial products release the massive amount of engineered nanoparticles (ENPs) in the environment. An increasing number of recent studies have shown the toxic effects of ENPs on different organisms, raising concerns over the nano-pollutants behavior and fate in the various environmental compartments. After the release of ENPs in the environment, ENPs interact with various components of the environment and undergoes dynamic transformation processes. This review focus on ENPs transformations in the various environmental compartments. The transformation processes of ENPs are interrelated to multiple environmental aspects. Physical, chemical and biological processes such as the homo- or hetero-agglomeration, dissolution/sedimentation, adsorption, oxidation, reduction, sulfidation, photochemically and biologically mediated reactions mainly occur in the environment consequently changes the mobility and bioavailability of ENPs. Physico-chemical characteristics of ENPs (particle size, surface area, zeta potential/surface charge, colloidal stability, and core-shell composition) and environmental conditions (pH, ionic strength, organic and inorganic colloids, temperature, etc .) are the most important parameters which regulated the ENPs environmental transformations. Meanwhile, in the environment, organisms encountered multiple transformed ENPs rather than the pristine nanomaterials due to their interactions with various environmental materials and other pollutants. Thus it is the utmost importance to study the behavior of transformed ENPs to understand their environmental fate, bioavailability, and mode of toxicity.